Optimalisasi Penyuluhan, Pemeriksaan, Pengobatan Penderita Hipertensi Sebagai Penyakit Utama Lansia Di Desa Sementara, Kecamatan Pantai Cermin Serdang Bedagai - Ismail, Wan Muhammad; Siregar, Nondang Purnama; Pasaribu, Saadatur Rizqillah; Ridhotullah, Muhammad Akthar; Br. Sitepu, Gethrain Sri Yuliani; Sartika, Sartika; Susani, Susani; Azzhura, Vanissa; Lubis, Mohd.Raudhi Dahlan; Fitrah, Rizky Maulana; Nasution, Alya Nuraini; Rifka A, Cut; Eka M, Nabila (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension is a disease suffered by one billion people in the world, including 2/3 of Hypertension sufferers who are in developing countries. This hypertension often occurs in adults but is more susceptible to Blood pressure if it is continuously high can cause damage to blood vessels, kidneys, heart, and circulation or even death This community service activity aims to provide education to 25 temporary village residents of Pantai Cermin Serdang Bedagai about prevention, early detection and treatment of Hypertension which is the main disease of the elderly. From the results of this service, the temporary village community who experienced the most mild Hypertension was 48% and consumed a lot of salt and excessive fat as much as 52%, the community experienced Obesity II excess weight by 44%, elderly age by 40%, female gender by 84%, had no history of hypertension in their families by 68%. with the status of elementary school/MI education level of 64%, Pretest score <70 as many as 10 people (40%), pretest score >70 as many as 15 people (60%) then Post test score <70 as many as 1 person (4%) and post test score >70 as many as 24 people (96%). There was an increase in the value of health education knowledge about Hypertension after the counseling was carried out